THE EFFECT OF INTEREST RATE OF CREDIT AND THIRD PARTY FUNDS ON THE NUMBER OF CREDIT DISTRIBUTION AT NATIONAL PRIVATE COMMERCIAL BANKS IN INDONESIA, 2015- 2019 - Wiralaga, Harya Kuncara; Sebayang, Karuniana Dianta; Nurlatifah, Dewi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of interest rates on loans and third party funds at National Private Commercial Banks in Indonesia in 2015-2019. The sampling technique uses purposive sampling method. The sample in this study consisted of 39 banks. The data analysis technique used in this research is multiple linear regression analysis, classic assumption test which includes normality test, multicollinearity test and heteroscedasticity test and hypothesis test including t test, f test and coefficient of determination. The model used in this study is the Fixed Effect Model. The results of the researchj show that the lending rate has a significant negative effect on the amount of credit disbursement, while third party funds have a significant positive effect on the amount of lending.